Implementation of Sufism Values in Islamic Education to Improve Mental Well-being of 21st Century Students - Hamdiani Hamdiani; Imaduddin Imaduddin (Islamic Religious Education Master Program Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Islamic education in the era of globalization faces various significant challenges, especially related to the decline in morals and mental well-being of students. Globalization brings social and cultural changes that can affect the character of the younger generation, so an appropriate approach is needed to deal with it. In this context, Sufism values ​​emerge as an alternative to improve mental well-being and the formation of positive character. This study aims to explore the application of Sufism values ​​in Islamic education to improve the mental well-being of students in the 21st century. The method used in this study is a literature study that examines various literature related to Sufism and mental well-being. The results of the study indicate that the integration of Sufism values ​​such as tawakal, sabar, ikhlas, and dhikr in Islamic education contributes positively to the mental well-being of students. In addition, the application of these values ​​helps students cope with the social and academic pressures they face while strengthening their character and morals. This study also found that students who apply Sufism values ​​tend to have better social relationships and are able to manage stress more effectively. The contribution of this study provides guidance for educational institutions to develop a curriculum that combines academic education and spiritual values.